Indonesian National Tin Production Planning: Conceptual Framework - Hadi Sahal Fadly Daulay; Andri Budhiman Firmanto; Yoke Pribadi Kornarius (Publikasi Indonesia, 2023)
Tin mining in Indonesia has been regulated by Indonesia Law Number 3 of 2020. However, it has not been fully utilized in Indonesia despite the country's abundant tin deposit opportunities, its position as one of the significant producers of tin globally, and the impact on both the global tin stock and price. In light of this, a comprehensive literature review has been carried out; an initial conceptual framework and causal loop diagram of Indonesia’s national tin production planning have been produced to produce the concept of an instrument for setting national tin production quotas and the concept of formulating the distribution of national tin production levels that could be a reference for future researchers as well as Government of Indonesia in order to find the national tin production planning.